Nursing Home Residents with Advanced Dementia and Persistent Vocalisations: Observations of Surrounding Context - Sefcik, Justine S. (Int J Older People Nurs, 2020)
PURPOSE: Persistent vocalisations are commonly exhibited by persons with dementia and are often characterized as agitation or aggression. There has been little focus on persistent vocalisations independent from other behavioural and psychological symptoms of dementia making it difficult to differentiate information about the context that surrounds the person with dementia, including the circumstances and events that precede and accompany the expression. Therefore, the aim of this study was to describe the context surrounding persistent vocalisations expressed by older adults residing in nursing homes (NH) with advanced dementia. DESIGN AND METHODS: The Need-driven Dementia-compromised Behaviour model informed this qualitative descriptive study. This naturalistic qualitative observational study involved direct observations of nine older adults diagnosed with dementia residing in four NHs and included informal interviews with formal caregivers. Field notes were taken and analysed using conventional content analysis. RESULTS: Variability of exhibited persistent vocalisations was both observed by the investigator and explained by NH staff. Two themes emerged from the field notes; Routine of Staying in Room was identified for participants considered “disruptive” to others, and Providing Care Without Communicating triggered persistent vocalisations. IMPLICATIONS: The findings provide insight into the lack of therapeutic interactions between NH staff and persons with advanced dementia and persistent vocalisations residing in NHs. Ongoing, mandatory, evidence-based training on person-centred interventions and dementia care communication for all NH staff globally could have a significant impact on the delivery of holistic quality care for persons with dementia and persistent vocalisations.